Depositional architectures and evolutional processes of channel systems in lacustrine rift basins: The Eocene Shahejie Formation, Zhanhua depression, Bohai Bay Basin. (September 2021) - Liu, Lei; Wen, Huaguo; Chen, Hongde; Wang, Zhiwei; Xu, Wenli
Abstract: Channels are considered effective conduits that deliver terrigenous sediments into related depositional basins, and they are the targets of petroleum exploration and production. Three-dimensional (3D) seismic data, well data, and attribute maps were used to study five types of channels observed in the Shahejie Formation of the Zhanhua Depression, namely erosional channels, confined channels, semi-confined channels, distributary channels, and transitional channels. The channels originated from hyperpycnal flows related to bed load, suspended load, and lofting processes from proximal to distal regions, which were primarily accumulated on medium and low terrains. The hyperpycnal channel systems were primarily identified as three stages with morphological changes in the Es3l and Es3m intervals on a seismic section. Stage 1 was developed during the late period of the Es3l interval, and stages 2 and 3 were developed during the early and middle periods, respectively, of the Es3m interval. Stage 1 is the initial/young stage formed during a phase of low accommodation. Channels of stage 1 are predominantly entrenched with moderately aggregated width and thick channelized splays. Stage 2 is the transitional stage formed during a phase of increasing accommodation. Channels of stage 2 are predominantly meandering with narrowly aggregated width and dispersed frontal splays. Stage 3 is a waned stage, formed during the events of increasing lake levels without comparable increase in sediment flux. This stage involves slight incisions, broad U-shaped morphology channels, and the prevalence of overbank sediments. The depositional architectures, processes, and the development of hyperpycnal channel systems correspond with the lake level and climate conditions of the proposed stages and were controlled by tectonic activity and source supply. Understanding the distribution and development of lacustrine hyperpycnal channels is important to improve and enrich theories of lacustrine sediment gravity flow. Highlights: Five types of channels were identified in the Shahejie Formation of the Zhanhua Depression. Hyperpycnal channel systems, consisted by five types of channels, were categorized as three stages. Tectonic activity, sediment supply, climate conditions, and lake level were demonstrated as the factors controlling the evolution of the lacustrine hyperpycnal channel system.